Maternal iron status during pregnancy compared with neonatal iron status better predicts placental iron transporter expression in humans. Issue 10 (11th July 2016) - Best, Cora M.; Pressman, Eva K.; Cao, Chang; Cooper, Elizabeth; Guillet, Ronnie; Yost, Olivia L.; Galati, Jonathan; Kent, Tera R.; O'Brien, Kimberly O.
ABSTRACT: The placenta richly expresses nonheme and heme Fe transport proteins. To address the impact of maternal and neonatal Fe status and hepcidin on the regulation of these proteins, mRNA expression and protein abundance of nonheme and heme Fe transport proteins were evaluated in placental tissue from 154 adolescents. Regression analyses found maternal Fe status was significantly associated with multiple placental nonheme and heme transporters, whereas neonatal Fe status was related to only 3 heme transporters. Across statistical analyses, maternal Fe status was consistently associated with the placental nonheme Fe importer transferrin receptor 1 (TfR1). Protein abundance of TfR1 was related to midgestation maternal serum ferritin (SF) (β = 20.32; P = 0.005) and serum TfR (β = 0.25; P = 0.024). Protein abundance of the heme importer, proton‐coupled folate transporter, was related to neonatal SF (b =0.30; P = 0.016) and serum TfR (β = 20.46; P <0.0001). Neonatal SF was also related to mRNA expression of the heme exporter feline leukemia virus subgroup C receptor 1 (β = 20.30; P = 0.004). In summary, maternal Fe insufficiency during pregnancy predicts increased expression of the placental nonheme Fe transporter TfR1. Associations between placental heme Fe transporters and neonatal Fe status require further study.—Best, C.M., Pressman, E.K., Cao, C., Cooper, E., Guillet, R., Yost, O. L., Galati, J., Kent, T. R., O'Brien, K.O. Maternal iron status during pregnancy compared with neonatal iron status better predicts placental iron transporter expression in humans. FASEB J. 30, 3541–3550 (2016). www.fasebj.org